AMBIENT SEISMIC NOISE VARIATIONS BEFORE EARTHQUAKES IN THE BAIKAL RIFT SYSTEM - S. A. Korol; A. V. Sankov; A. A. Dobrynina; V. A. Sankov (Геодинамика и тектонофизика)
This paper proposes a method to observe the pre-earthquake features based on the variations in ambient noises using local moderate and strong seismic events as an example. Eight earthquakes in the Baikal rift system with energy classes K=10.1–15.9 were associated to a significant decrease in the level of ambient noises at epicentral distances from 3 to 81 km a few hours before the shock. The observed decrease in the ambient noise level can be classified as a short-term precursor of the medium consolidation 4–5 hours before the earthquake.